The Contribution of Principal’s Managerial Competence and Teacher Performance to the Quality of Vocational Education in Mataram City - Teguh Viras Mannic; Sudirman Wilian; Abdul Kadir Jaelani; Heri Hadi Saputra; Muhammad Makki (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2026)
This study goals to determine the extent to which the managerial competence of school principals and teacher performance influence the quality of education at State Vocational High Schools (SMKN) in Mataram City. This study applies a mixed methods approach with an explanatory sequential design involving 562 teachers from seven vocational high schools in Mataram City, with 85 teachers selected through purposive sampling. Data were acquired through questionnaires, observations, interviews, and documentation. The results indicate that principal managerial competence has a significant but small contribution on education quality, as shown by a significance value of 0.037 (< 0.05) and an effect size of 0.052. In contrast, teacher performance demonstrates a significant and moderate contribution, with a significance value of 0.000 (< 0.05) and an effect size of 0.266. Moreover, both variables simultaneously show a strong and significant contribution to education quality, supported by an F-test significance of 0.000 (< 0.05) and a combined effect size of 0.417, indicating a moderate contribution